Frédéric Barbier, The Greek Dream by Monsieur de Choiseul: The Travels of a European of the Enlightenment. [Review of the Book: Le rêve grec de Monsieur de Choiseul Les voyages d'un européen des Lumières by Frédéric Barbier] - Irene Kamberidou (Journal of Modern Greek Studies (Print ISSN: 0738-1727, Online ISSN: 1086-3265), 2018)
John Hopkins University Press:  (PROJECT MUSE: https://muse.jhu.edu/article/671081) Irene Kamberidou (2017). Journal of Modern Greek Studies, Volume 35, Number 2, October 2017, pp. 564-570 | 10.1353/mgs.2017.0031        [[Praised as "a magnificent scholarly journal" by Choice magazine, Journal of Modern Greek Studies is the only scholarly periodical to focus exclusively on modern Greece. The Journal publishes critical analyses of Greek social, cultural, and political affairs, covering the period from the late Byzantine Empire to the present. Contributors include internationally recognized scholars in the fields of history, literature, anthropology, political science, Byzantine studies, and modern Greece. Journal of Modern Greek Studies is the official publication of the Modern Greek Studies Association (MGSA).]]..............ARTICLE CITATION:  Kamberidou, Irene (2017). Frédéric Barbier, The Greek Dream by Monsieur de Choiseul: The Travels of a European of the Enlightenment. [Review of the Book:  Le rêve grec de Monsieur de Choiseul Les voyages d'un européen des Lumières by Frédéric Barbier] Journal of Modern Greek Studies 35 (2017) 564–612 © 2017 by The Modern Greek Studies Association. Print ISSN: 0738-1727,  Online ISSN:  1086-3265. John Hopkins University Press: https://www.p      ***** The Greek Dream by Monsieur de Choiseul: The Travels of a European of the Enlightenment by Frédéric Barbier Journal Article published 2017 in Journal of Modern Greek Studies volume 35 issue 2 on pages 564 to 570 Author: Irene Kamberidou  https://doi.org/10.1353/mgs.2017.0031  , John Hopkins University Press